Prognostic role of FEV1 for survival in bronchiolitis obliterans syndrome after allogeneic hematopoietic stem cell transplantation. (30th October 2015) - Ahn, Jee Hwan; Jo, Kyung‐Wook; Song, Jin Woo; Shim, Tae Sun; Lee, Sei Won; Lee, Jae Seung; Kim, Dae‐Young; Lee, Je‐Hwan; Lee, Jung‐Hee; Choi, Yunsuk; Lee, Kyoo‐Hyung
Abstract: Background: Bronchiolitis obliterans syndrome (BOS) can occur after hematopoietic stem cell transplantation (HSCT) and is associated with significant mortality. We investigated the role of forced expiratory volume in one s (FEV1 ) as a prognostic marker in BOS after HSCT. Methods: Among all patients who underwent HSCT between December 1993 and November 2013 at a tertiary center in South Korea, 1187 patients were enrolled. Patient medical records were retrospectively analyzed to evaluate the prognostic factors associated with survival in these cases. Results: During a median follow‐up period of 30.7 months after HSCT, 82 patients (6.9%) were diagnosed with BOS. The mean FEV1 of the BOS patients was 34.7% of predicted, and the mean FEV1 of 31 of these patients (37.8%) was <30% of predicted. The estimated overall survival rate for BOS patients excluding three patients who received lung transplantation was 74% at three yr from BOS diagnosis. Multivariate analysis showed that diagnosis of BOS within six months and FEV1 < 30% of predicted at the time of BOS diagnosis were associated with shorter survival. Conclusions: An FEV1 < 30% of predicted at the time of diagnosis is significantly associated with an increased risk of death in patients with BOS after HSCT.